Effect of Basic Pharmacotherapy on the State of Cerebral Hemodynamics in Children with Bronchial Asthma - O.Yu. Akulova; S.M. Nedelska (Zaslavsky O.Yu., 2015)
The article analyzes the impact of basic pharmacotherapy on the state of extra- and intracranial cerebral hemodynamics in children with bronchial asthma (BA). Monotherapy with antileukotriene drugs normalizes the greatest number of cerebral hemodynamics parameters, the next one - combination treatment with glucocorticosteroid and antileukotriene drugs, the least effective is basic inhaled glucocorticosteroid therapy. None of the analyzed schemes helps to eliminate the phenomena of hypoperfusion in the vertebrobasilar zone in children with BA. During remission, several indicators of cerebral hemodynamics, relating to which all of these schemes of basic pharmacotherapy for BA were effective, worsened and didn't differ statistically from similar indicators in patients with uncontrolled BA. Children with BA should be supervised by pediatric neurologist and require follow-up Doppler examination of the great vessels of the head and neck regardless of the degree of underlying disease control.